Teachers’ alignment between a local initiated external assessment: The diagnostic literacy test—And teaching regarding special educational needs students’ needs - Sjunnesson, Helena (Frontiers in Education, 2022)
The present study aims to study how external assessments are used by teachers, transforming summative test results into a formative approach for teaching, with a special focus on students with SEN. The data material consists of documents and interviews with teachers. The documents were the schools’ compilations of assessment results, including proposals for measures and action programs for individual students. The students’ action programs constitute data material for analysis of their needs regarding the outcomes of the DLS tests. Eight ordinary and six SEN teachers participated in follow-up interviews to express their understanding of the test results and their decisions regarding what adaptations and support the students needed. The results show the teachers’ expressions and understanding of aligning the results to better support the identified SEN students in education. The emerging results indicate that the primary purpose of the assessment was to identify students with SEN and to plan teaching for these students. SEN was identified by test results on or below stanine 3. The planned support was mainly directed toward special education conducted by SEN teachers. Within the same community, different interpretations of the assignment are possible. This may affect how the results are analyzed and implemented into teaching.